YouTubeTM as a source of patient information for ureteroscopy. (July 2016) - Abboudi, Hamid; Mikhail, Michael; Ghazal-Aswad, Mohammed; Michael, Michael; Pope, Alvan
Objective: YouTube TM has provided a platform that is utilised by millions. Patients are increasingly utilising this source of information. We set out to systematically analyse the quality of ureteroscopy videos. Materials and methods: YouTube TM was searched using the term 'ureteroscopy'. Content was assessed using the British Association of Urological Surgeons website criteria. Information relating to management options, procedural description, stent insertion, recovery and complications was rated. An overall rating was given. Videos were also analysed in terms of country of origin, view count, likes, dislikes, source and technical quality. The kappa statistic was used. Results: A total of 59 videos were analysed. The total number of viewings was 557, 896 (range: 42– 121, 943), with an average number of 9456 viewings per video. The information content was either poor or average in 98% ( n = 58) of videos, with only 2% ( n =1) rated as good and 0% achieving an excellent rating. Technical quality was rated as poor in 28 videos, average in 22 and good in nine videos. Most videos were broadcast by surgeons or surgical institutes (48/59). Conclusion: The quality of videos is variable. Patients should not be encouraged to use this for education. Opportunity has arisen for the endourology community to produce high quality video broadcasts to optimise patient understanding.